Peran Kolaborasi Model Creative Problem Solving Dan Pembelajaran Metode Team Kuis Dalam Meningkatkan Berpikir Kreatif di SDN Ibu Dewi 3 Cianjur - Moh. Jailani; Sulis Tyaningsih; Siti Qomariyah (Lembaga Pengembangan Kinerja Dosen, 2023)
Education is a conscious effort to change character, morals, morals and also fosters creativity in thinking. Creative in thinking is something that is very urgent in life. Education has value to be able to solve problems precisely and quickly. The purpose of this study was to determine the extent to which the Collaborative Role of Creative Problem Solving and the Quiz Team Method played a role in increasing creative thinking. This study uses a qualitative descriptive analytical approach, which is one of the approaches used in qualitative research to understand phenomena in detail and depth. Researchers collect data through interview techniques, observation, case studies, or document analysis. Researchers used the class action research method (CAR). CAR involves iterative cycles of planning, action, observation, and reflection in order to achieve continuous improvement in student learning and achievement. The results showed that learning Creative Problem Solving (CPS) and quiz teams can improve students' creative thinking and this method is very good to use because students feel happy and not bored.